2019
DOI: 10.3390/ijgi8040193
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Multi-Sensor-Derived Heights and OSM-Derived Building Footprints for Urban 3D Reconstruction

Abstract: So-called prismatic 3D building models, following the level-of-detail (LOD) 1 of the OGC City Geography Markup Language (CityGML) standard, are usually generated automatically by combining building footprints with height values. Typically, high-resolution digital elevation models (DEMs) or dense LiDAR point clouds are used to generate these building models. However, high-resolution LiDAR data are usually not available with extensive coverage, whereas globally available DEM data are often not detailed and accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The recently available satellite-derived elevation datasets provide an opportunity for data fusion by incorporating the elevation data with open-licensed 2D building data to generate 3D models. Indeed Bagheri et al generated LOD1 height values using multisensor and multimodal DEM fusion techniques-TanDEM-X DEM and Cartosat-1 DEM data were joined with OpenStreetMap building footprints [24]. This study confirmed that simple, prismatic building models can be reconstructed by combining OpenStreetMap building footprints with remote sensing-derived geodata.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…The recently available satellite-derived elevation datasets provide an opportunity for data fusion by incorporating the elevation data with open-licensed 2D building data to generate 3D models. Indeed Bagheri et al generated LOD1 height values using multisensor and multimodal DEM fusion techniques-TanDEM-X DEM and Cartosat-1 DEM data were joined with OpenStreetMap building footprints [24]. This study confirmed that simple, prismatic building models can be reconstructed by combining OpenStreetMap building footprints with remote sensing-derived geodata.…”
Section: Introductionsupporting
confidence: 58%
“…To the authors' knowledge, this is the first attempt at combining OSM data with AW3D data to generate 3D models. We built upon previous studies that fused OSM with satellite-derived elevation data [24], however in our study, we provided a method to generate 3D models for both flat and undulated terrain using open data, which makes it feasible to replicate globally with any kind of terrain. Our study also demonstrated ways to increase the accuracy of the generated 3D city models using a sample high resolution DSM and DTM data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sources are the Istanbul Metropolitan authority, OSM, TomTom and Basarsoft (both of the latter are private navigation data). 3D Reconstruction [34]: prismatic 3D building models are built by adding height values to a 2D footprint (source: OSM). The heights are computed with two different approaches, depending on the availability of sources providing a sufficient high-resolution spatial coverage at an urban scale.…”
mentioning
confidence: 99%